1999
DOI: 10.1038/sj.bjc.6690530
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vascular endothelial growth factor, matrix metalloproteinase-9 and E-cadherin in the process of lymph node metastasis in oesophageal cancer

Abstract: Lymph node metastasis is a strong independent prognostic factor for oesophageal cancer. The expression of matrix metalloproteinases (MMPs) and reduction of E-cadherin correlate with lymph node metastasis of oesophageal cancer. We previously reported that the expression of vascular endothelial growth factor (VEGF) is associated with lymph node metastasis. This study was designed to determine whether VEGF, MMP-9 and E-cadherin expression is stable or changes in the process of lymph node metastasis of oesophageal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 36 publications
(31 reference statements)
4
54
2
Order By: Relevance
“…The association of angiogenic factor expression with a high incidence of treatment failure may contribute to the resistance to therapy observed in both the TP-ICH-and VEGF-ICH-positive groups. The duration to treatment failure and the treatment response rates were significantly poorer in the VEGF-ICH-positive group compared to the VEGF-IHC-negative group, and thus would eventually lead to poorer survival, as reported previously (Kitadai et al, 1998;Sato et al, 1999;Shih et al, 2000). Blocking VEGF activity was reported to enhance the anti-tumour effects of ionizing radiation (Gorski et al, 1999).…”
Section: Molecular and Cellular Pathologysupporting
confidence: 78%
See 1 more Smart Citation
“…The association of angiogenic factor expression with a high incidence of treatment failure may contribute to the resistance to therapy observed in both the TP-ICH-and VEGF-ICH-positive groups. The duration to treatment failure and the treatment response rates were significantly poorer in the VEGF-ICH-positive group compared to the VEGF-IHC-negative group, and thus would eventually lead to poorer survival, as reported previously (Kitadai et al, 1998;Sato et al, 1999;Shih et al, 2000). Blocking VEGF activity was reported to enhance the anti-tumour effects of ionizing radiation (Gorski et al, 1999).…”
Section: Molecular and Cellular Pathologysupporting
confidence: 78%
“…VEGF induction and vascularization of solid tumours has been shown to play an important role in the response to chemotherapeutic agents and radiation therapy (Shintani et al, 2000;Veikkola et al, 2000;Volm and Rittgen, 2000). Immunohistochemical (IHC) analyses of oesophageal carcinoma have revealed that angiogenesis, as determined by micro-vessel density, is a prognostic factor (Inoue et al, 1997;Kitadai et al, 1998;Sato et al, 1999;Shih et al, 2000). Over-expression of VEGF protein is, therefore, at least partially responsible for the malignant potential in oesophageal cancer and represents a useful prognostic marker.…”
mentioning
confidence: 99%
“…This is associated with down-regulation of E-cadherin expression (Novak et al, 1998;Wu et al, 1998). It has been shown previously that loss of expression of the cell adhesion molecule E-cadherin is correlated with increased MMP-9 expression in invasion and metastasis (Sato et al, 1999;Llorens et al, 1998;Luo et al, 1999). We now report that overexpression of ILK in rat intestinal epithelial IEC18 cells as well as in mouse mammary epithelial scp2 cells results in increased MMP-9 expression.…”
Section: Discussionmentioning
confidence: 88%
“…The progression and invasion capacity of tumor is associated to with the degradations of basement membrane (which is formed by Type IV collagen), and the fibrous capsule (which is formed by Type I and Type III collagen). Due to the proteolytic activity of MMP-9 enzyme that degrades type IV collagen, it increases tumor invasion and progression (Shima et al, 1992;Kusukawa et al, 1993;Sato et al, 1999) Hong et al (2000) found the significant relationship between MMP-9 expression and cervical metastatic disease. The increased expression of MMP-9 in patients with oral squamous cell carcinoma was stated as 73.7% in contrast with our study, and any correlation with decrease in histological differentiation has not been established.…”
Section: Figure 3 A) the Staining Of Normal Epithelial Tissue For E-mentioning
confidence: 99%